Nano-sized particles emission during drilling and low velocity impact of silica-based thermoplastic nanocomposites - Sachse, Sophia (Cranfield University, 2012)
During the past decade, polymer nanocomposites have emerged as a novel and rapidly developing class of materials and attracted considerable investment in research and development worldwide. Driven by the certainty that by the integration of low nano ller amounts, existing material properties can be improved and moreover new material properties can be developed. Despite the clear bene t and therefore, increasing research, production and utilisation of nanomaterials, little is known about how nanocomposites will perform over their whole life cycle, especially in the usage and end of life phase. Under the in uence of environmental factors such as ultraviolet light, moisture, temperature and mechanical actions, nano-sized particles can be potentially released from nanocomposites and thus may have negative e ects on the human health and the environment. Within the scope of this work an extensive literature review has been conducted in which polymer nanocomposites are brie y introduced and release scenarios of engineered nano-sized particles from nanocomposites during their life cycle are discussed. In the experimental part of this work silica based polypropylene, polyamide and polyurethane composites were manufactured and particle exposure mechanism during mechanical processing and testing were monitored and analysed. A series of comprehensive physical characterisation techniques were utilised to assess particle size distribution, shape, and concentration in di erent mediums, once emitted by the solid composite materials. It was observed that during drilling of PA6 composites, the airborne particle emission rates were 10 times higher than those for the PP based composites. However, the characterisation of deposited particles showed exactly the opposite behaviour, were the total number of particles emitted by the PP based composites was 10-100 times higher than those of the PA6 based composites. To the best of our knowledge, this is the rst time such work has been reported in the literature. Further, the addition of secondary ller into a polymer/glass- bre composites changed the micro-mechanism during crash testing and therefore controlled the energy absorption characteristics of the composites. However, it was shown that once subjected to higher impact energies the geometric particle size of the released particles increased from approx. 25 nm for the 530 J to approx. 60 nm for the 1560 J impact. Additionally, the tensile modulus increased by 0.31 GPa and the speci c energy absorbed during impact test increased from 20.7 kJ to 22.6 kJ by using nano-SiO2 alternative to micro-SiO2 particles in PP/glass- bre matrix. Even though a respective enhancement in mechanical properties were observed by using nano llers over micro llers, no signi cant di erence in particle emission during impact test were measured. Further, it could be shown that during drilling and testing, nano-sized particles were released from all materials studied, regardless of whether they had nanoparticles integrated or not. In one particular case, the neat polymer matrix generated more nano-sized particles during drilling than the exfoliated PA6/nanoclay nanocomposite. Hence, the addition of nanoclay can have bene cial impact in terms of controlled particle release. However, in general the addition of nano llers increased the particle emission rates during drilling and impact testing of the nanocomposites. Further, the emitted nano-sized particles were not all free engineered pristine nanoparticles but also hybrid particles consisting of matrix/nano ller material. A signi cant set of data was obtained during this study and hence the outcomes sets an excellent foundation for risk assessment and life cycle analysis of silica based polypropylene, polyamide and polyurethane nanocomposites.